Could biochemical liver profile help to assess metabolic response to aerobic effort in athletes? - Chamera, T.; Spieszny, M.; Klocek, T.; Kostrzewa-Nowak, D.; Nowak, R.; Lachowicz, M.; Buryta, R.; Cieszczyk, P. (The Journal of Strength and Conditioning Research, 2014)
Monitoring and optimizing the effectiveness of training course require wide analyses of athletes' blood parameter changes. The aim of this study was to evaluate the usefulness of biochemical liver profile to assess the metabolic response to semi-long-distance outdoor run in football players. Sixteen football players run outdoor for 60 minutes to achieve aerobic metabolism. Plasma activity of aspartate aminotransferase (AST), alanine aminotransferase (ALT), Gamma-glutamyltransferase (GGT) and plasma levels of total and direct bilirubin were determined in samples obtained before exercise test (pre-exercise) and immediately after the run (post-exercise). Mean AST plasma activity (U·L-1) before/after the exercise, respectively, was 78.3/228.3 in women and 76.5/56.2 in men. Mean ALT plasma activity (U·L-1) before/after the exercise, respectively, was 27.5/59.1 in women and 36.2/35.3 in men. Mean GGT plasma activity (U·L-1) before/after the exercise, respectively, was 39.3/76.6 in women and 44.7/71.2 in men. Plasma levels of total and direct bilirubin were similar before and after the run regardless of the gender. Statistical significance of the differences between results obtained pre- and post-exercise occurred in women (p = 0.0212 for AST; p = 0.0320 for ALT; p = 0.0067 for GGT, respectively). The training monitoring in athletes should be performed using measurements of performance and biological or physiological parameters. It was found that AST, ALT, and GGT activities could be a valuable tool to assess the metabolic response in high-level fitness female athletes. Therefore, monitoring of those well-known diagnostic markers could prevent the trainee from harmful overtraining.